What does the future hold for compressor manufacturers?. (May 2015) - Pearson, Andy
This paper explores some future opportunities in refrigeration for compressor designers and manufacturers. Some of the most interesting concepts are in expanders and, in particular, how to integrate them into systems, how to target suitable applications and how to convince non-technicians that this is necessary and worthwhile. In some cases, the compressor may hold the key to a problem experienced in another part of the system; at other times, the solution to a compressor design challenge may be found by making changes elsewhere.